Descripción morfológica y biomecánica de la articulación de la rodilla del canino (Canis lupus familiaris) - Saldivia Paredes, Manuel (2018)
Abstract The synovial joints, or also known as diarthroids, are characterized by their high mobility, constituted by a protective joint capsule, which in turn internally allows the formation of a cavity, where it is possible to observe synovial fluid, responsible for providing Nutritional elements; Purifying cell debris; Make a damping between the articular faces and lubricate the articular surfaces. The knee is one of the largest synovial joints in the body and one of the most complex is its morphology and biomechanics. Its anatomical conformation consists of the union of bony, cartilaginous, ligamentous, vascular and muscular structures that allow to grant a specific functionality in its extensor, flexor and slight rotation capacity. Therefore, the objective of the following study was to perform a morphological description of the macroscopic anatomical structures, which participate in the conformation of the knee joint and how they can allow a particular biomechanical functionality. For this, dissections of 10 knees of male dogs were carried out in the veterinary anatomy laboratory of the Universidad Santo Tomas, Puerto Montt. The results indicate detailed characteristics of the canine knee morphology and how each of them allows to understand and explain the biomechanical capacity of this joint. Resumo Articulações sinoviais ou também conhecido como diartroideas são caracterizados por uma elevada mobilidade, ser constituído por uma cápsula da articulação de protecção, o que por sua vez permite que internamente a formação de uma cavidade, onde se pode observar o fluido sinovial, responsável pelo fornecimento de elementos nutrientes; produzir a purificação do lixo celular; faça um amortecimento entre as faces das juntas e lubrifique as superfícies das juntas. O joelho é uma das maiores articulações sinoviais do corpo e uma das mais complexas em sua morfologia e biomecânica. conformação anatómica consiste na união de osso, cartilagem, ligamentos, estruturas vasculares e musculares que permitem dar uma ...